Intermittent electrical stimulation removes mixed antibiotics and associated antibiotic resistance genes at low temperatures - Chaoyue He; Nuerla Ailijiang; Zaimire Abdusalam; Yincang Cui; Na Li; Mei Wu; Hailiang Chen; Yiming Zhang (Emerging Contaminants)
Biotechnology has limited effectiveness in terms of removing mixed antibiotics at low temperatures, leading to ecological risks arising from the presence of antibiotics in environmental waters. In this study, the removal of tetracycline (TCs) and sulfonamide (SAs) from antibiotic wastewater was improved by the intermittent electrical stimulation of anaerobic-aerobic-coupled upflow bioelectrochemical reactors (AO-UBERs) at low temperatures. The removal effects of oxytetracycline and tetracycline were 48.6 ± 3.5 % and 71.5 ± 2.9 %, respectively. Under 0.9V, the removal rates of oxytetracycline, tetracycline, and trimethoprim were significantly increased in both the aerobic-cathodic and anaerobic anodic chambers, with a more obvious increase at low temperatures. Compared with the blank control group, the removal efficiency of oxytetracycline, trimethoprim and tetracycline in the electric group was increased by 11.8 ± 2.5 %, 27.8 ± 10.5 % and 11.2 ± 5.8 %. The anaerobic chamber contributed more to the removal of TCs and trimethoprim than the aerobic chamber. Furthermore, electrical stimulation selectively enriched electroactive bacteria (Methylophage and Pleuromonas), drug-resistant bacteria (Proteobacteria), and nitrifying bacteria associated with biodegradation. The abundance of antibiotic-resistance genes is related to the distribution of potential hosts and mobile genetic elements (sul1), and electrical stimulation induces the enrichment of both. This suggests that while potentially effective for treating TCs- and SAs-containing wastewater at low temperatures, AO-UBERs may lead to the accumulation of antibiotic-resistance genes.